Diaphragmatic Dysfunction after Thoracic Operations - Gaissert, Henning; Wilcox, Susan R. (The Thoracic and Cardiovascular Surgeon, 2016)
The perioperative management of diaphragmatic weakness and phrenic nerve dysfunction is complex, due to varied etiologies and clinical presentations. The factors leading to diaphragmatic weakness may culminate after the operation with transient or persistent respiratory failure. This review discusses diaphragmatic disorders and postoperative respiratory failure caused by unilateral or bilateral diaphragmatic impairment. The origins of neuromuscular weakness involving the diaphragm are diverse, and often lie within the domains of different medical specialties, with only a portion of the condition related to surgical intervention. Consideration of underlying etiologies for any individual patient requires thorough multidisciplinary review. The most important clinical scenarios compounding diaphragmatic weakness, including acute myasthenic states, persistent neuromuscular blockade, and surgical injury to the phrenic nerve or diaphragm, are accessible to attentive surgeons. Awareness of the signs and symptoms of undiagnosed weakness, preoperative pursuit of its diagnosis, knowledge of surgical alternatives to phrenic nerve resection, and cooperative skills in the multidisciplinary management of myasthenia all are crucial to improve patient outcomes.
Keywords: diaphragm; myasthenia; respiratory failure; thymoma; neuromuscular disease